Endapan Kipas Aluvial di Daerah Bukitlawang, Sumatra Utara Berdasarkan Interpretasi Citra Landsat ETM7 dan IFSAR - Faturrakhman, Muhammad Luthfi; Agustin, Fitriani (Pusat Survei Geologi, 2017)
Bukitlawang alluvial fan deposit formed, North Sumatra is one of the geomorphological aspect that can be observed in landsat and radar images. Flow direction of the alluvial fan is from west to east with having the total distribution of 77 Km2. Sumatra fault which is located at the eastern side of it plays a major role in the formation of alluvial fan deposit in this area. The type of alluvial fan is debris flow with the primary sedimentary process is a debris flow deposit.Keyword : Bukitlawang alluvial fan, Sumatra fault, Geomorphology, Radar – Landsat images.